Stabilizing effect of the rib cage on adjacent segment motion following thoracolumbar posterior fixation of the human thoracic cadaveric spine: A biomechanical study. (December 2019) - Rahm, Mark D.; Brooks, Daina M.; Harris, Jonathan A.; Hart, Robert A.; Hughes, Jessica L.; Ferrick, Bryan J.; Bucklen, Brandon S.
Abstract: Background: Although the rib cage provides substantial stability to the thoracic spine, few biomechanical studies have incorporated it into their testing model, and no studies have determined the influence of the rib cage on adjacent segment motion of long fusion constructs. The present biomechanical study aimed to determine the mechanical contribution of the intact rib cage during the testing of instrumented specimens. Methods: A cyclic loading (CL) protocol with instrumentation (T4–L2 pedicle screw-rod fixation) was conducted on five thoracic spines (C7–L2) with intact rib cages. Range of motion (±5 Nm pure moment) in flexion-extension, lateral bending, and axial rotation was captured for intact ribs, partial ribs, and no ribs conditions. Comparisons at the supra-adjacent (T2–T3), adjacent (T3–T4), first instrumented (T4–T5), and second instrumented (T5–T6) levels were made between conditions ( P  ≤ 0.05). Findings: A trend of increased motion at the adjacent level was seen for partial ribs and no ribs in all 3 bending modes. This trend was also observed at the supra-adjacent level for both conditions. No significant changes in motion compared to the intact ribs condition were seen at the first and second instrumented levels ( P  > 0.05). Interpretation: The segment adjacent to long fusion constructs, which may appear more grossly unstable when tested in the disarticulated spine, is reinforced by the rib cage. In order to avoid overestimating adjacent level motion, when testing the effectiveness of surgical techniques of the thoracic spine, inclusion of the rib cage may be warranted to better reflect clinical circumstances. Highlights: Motion was captured following T4–L2 instrumentation, with and without the rib cage. Contribution of the rib cage on segmental motion following instrumentation is limited. Removal of rib cage significantly affected adjacent and supra-adjacent level motion. Studies without the rib cage may overestimate adjacent level effect of long constructs.